Kartering av kadmiumhalt i matjord med portabelt röntgenfluorescensinstrument - Laxmar, Elin (SLU/Dept. of Soil and Environment, 2018)
Cadmium (Cd) is a nonessential heavy metal that can be toxic to living organisms even in small amounts. Cd occurs naturally in all type of soils but have also been added trough soil amendments and atmospheric fallout.